IMPLICATIONS OF DIFFERING HIV/AIDS - Pearce, Bronwyn (My University, 2011)
Prevention efforts in South Africa, despite increasing investment, have not positively impacted on prevalence rates. This research report sets out to determine the implications, if any, of differing communication strategies on prevention. The funding environment in which programmes strategies are developed and implemented are explored to determine if funding issues impact on programme strategies. Interviews were conducted with experts from the NGO sector, government as well as international donor organizations. In the absence of a clear national communications strategy there has been minimal impact on prevention. Key issues emerging from this research point to the lack of a national strategy and cohesion of programming, and the need to address the complexities of HIV communication. Going forward the importance of an inclusive strategy which is sound in its epidemiological understanding will be critical in providing a framework in which all communication programmes can contribute to reducing prevalence in South Africa.
MM - P&DM
Keywords: HIV/AIDS communication; HIV/AIDS prevention